2018
DOI: 10.5897/ajpp2018.4910
|View full text |Cite
|
Sign up to set email alerts
|

Utility of silver nanoparticles for the analysis of diosmin and rutin in Persicaria salicifolia extract, authentic and pharmaceutical dosage forms monitored with their haemostatic activity

Abstract: The present work was conducted to evaluate a simple effective technique for spectrophotometric determination of two flavonoids namely diosmin (1) and rutin (2) in the isolated fractions obtained from Persicaria salicifolia, authentic and pharmaceutical dosage forms, the method is based on the reduction of Ag + cations to silver nanoparticles (Ag-NPs) by the effect of these flavonoids in the presence of polyvinylpyrrolidone (PVP) as a stabilizing agent which result in production of intense brown colour correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A simplified mechanism for the green synthesis of the rGO-AuNP nanocomposite using the P. salicifolia extract is shown in Figure 1 according to which the simultaneous reduction of GO, which was obtained after the oxidation of graphite via the Hummers method, and Au 3+ into the rGO-AuNP nanocomposite was achieved through the active contribution of phytoconstituents including flavonoids, alkaloids, tannins, and other constituents that acted as a reducing and capping agent at the same time obviating the use of chemical reducing agents; these phytoconstituents were verified to be existent in the P. salicifolia extract by Youssef and El-Swaify 38 and Salem et al 39 In addition, these phytoconstituents were proven to be capable of donating electrons or hydrogen atoms to gold ions to get these ions reduced on the surface of the rGO. 40 These studies indicated the high efficacy of employing the aqueous extract of P. salicifolia in the biosynthesis of numerous metallic and nonmetallic nanomaterials, mainly P. salicifolia exposed to harsh environmental conditions like droughts and high salt concentrations as it has been proven that the concentration of phytoconstituents increases in most living plant species when the harshness of these environmental conditions increases.…”
Section: Resultsmentioning
confidence: 99%
“…A simplified mechanism for the green synthesis of the rGO-AuNP nanocomposite using the P. salicifolia extract is shown in Figure 1 according to which the simultaneous reduction of GO, which was obtained after the oxidation of graphite via the Hummers method, and Au 3+ into the rGO-AuNP nanocomposite was achieved through the active contribution of phytoconstituents including flavonoids, alkaloids, tannins, and other constituents that acted as a reducing and capping agent at the same time obviating the use of chemical reducing agents; these phytoconstituents were verified to be existent in the P. salicifolia extract by Youssef and El-Swaify 38 and Salem et al 39 In addition, these phytoconstituents were proven to be capable of donating electrons or hydrogen atoms to gold ions to get these ions reduced on the surface of the rGO. 40 These studies indicated the high efficacy of employing the aqueous extract of P. salicifolia in the biosynthesis of numerous metallic and nonmetallic nanomaterials, mainly P. salicifolia exposed to harsh environmental conditions like droughts and high salt concentrations as it has been proven that the concentration of phytoconstituents increases in most living plant species when the harshness of these environmental conditions increases.…”
Section: Resultsmentioning
confidence: 99%
“…415-432 [15] Tacrine Tacrine was formulated and loaded on poly(lactide-co-glycolide) nanoparticles in handling the alzheimer,s disease and were provided using modified nano precipitation technique. Pharmacodynamics studies of nanoparticles were estimated for brain and memory improvement in scopolamine motivated amnesic mice using morris water test and inhibitory step down avoidance.…”
Section: Spectrofluorimetric Methodsmentioning
confidence: 99%